Foreign investment and the domestic economy: The case of India - Gupta, Rajnarayan (The Indian Journal of Economics)
International capital flows have been increasing in the world since the initiation of globalisation. Capital flows into a country mainly in two channels. Typically, they are called -Foreign Direct Investment (FDI)- and -Foreign Portfolio Investment (FPI)-. Both have important impact on the host economy. The present study investigates into the role of foreign investment in the Indian economy and also the capacity of the host economy to attract those foreign funds. Vector Autoregressive Model (VAR) and Granger Causality Test have been applied for that purpose. The empirical findings assert the linkage between foreign investment and the domestic economy but the causality runs from the former to the latter and not the other way round. The vulnerability of the economy to international forces remains a cause for concern.- Reproduced
Keywords: Foreign direct investment, Foreign institutional investment, GDP, SENSEX, VAR, Granger causality